Young restored forests increase seedling recruitment in abandoned pastures in the Southern Atlantic rainforest - Flora H.M Leitão (Revista de Biología Tropical, 2010)
Planting seedlings is a common technique for abandoned pastures restoration in the tropics, supposedly by increasing the seedling recruitment and accelerating succession. In this study we evaluated the role of a young restored forest (one year old) in enhancing seedling establishment from two sources (seed rain and seed bank), in the Atlantic Rainforest region in Southern Brazil. We compared abandoned pasture, young restored forest and old-growth forest with respect to the seedlings recruited from different sources, by monitoring 40 permanent plots (0.5mx0.5m) over 20 months. From the three studied areas a total of 392 seedlings of 53 species were recruited. Species were mainly herbaceous (85%), pioneers (88%), zoochorous (51%) and small-seeded species (60%). Seedling recruitment from the seed bank (density and species richness) was higher and dominated by herbaceous species in the abandoned pasture and in the young restored forest; on the other hand, the recruitment of woody species from seed rain was more pronounced in the old-growth forest. The young restored forest increased the species richness of woody seedlings recruitment from the seed bank (two-fold) and from seed rain (three-fold) compared to the abandoned pasture. Also, the seedling density in young restored forest was still higher than abandoned pastures (seed bank: four times; seed rain: ten times). Our results show that even young restored areas enhance the establishment of woody species and should be considered an important step for pasture restoration. Rev. Biol. Trop. 58 (4): 1271-1282. Epub 2010 December 01.